Religiosity and sexual risk-taking : results from a 2010 population-based study of young Croatian adults - Landripet, Ivan (Array, 2010)
Background and objectives. Advocating abstinence from premarital sex and most forms of contraception, religious teachings may substantially affect sexual decision-making and behavior, particularly among young people. In terms of vulnerability to HIV and other STI, the influence could be twofold: religiosity may delay sexual debut and reduce number of sexual partners, but also hinder condom use. Our aim was to examine some of the possible sexual risk-reducing and risk-enhancing effects of religiosity among youth in one of many post-communist countries that experienced a strong increase both in religious identification and political/social influence of religious institutions. Design and methods. A household-based survey was carried out in February 2010 on a nationally representative probability sample of young men and women aged 18-25 (N=1, 005). Religiosity was measured both as religiousness (a 5-item personal religiosity scale together with religious celebration attendance) and religious upbringing (strict, formal or none). To evaluate the interplay between religiosity and STI/HIV-related sexual risk-taking, multiple logistic regressions were carried out with early sexual debut, condom use at first and most recent intercourse, and consistent use of condoms in the last 12 months as outcomes. Indicators of religiosity, age, personal and parental education, settlement type, parental control, intact family and knowledge of HIV/AIDS were included as covariates. Results. The likelihood of early sexual initiation (≤15) decreased with parental control (OR=.87, p<.05) in men and with personal religiosity (OR=.76, p<.05) in women. The odds of using condom at first sexual intercourse were associated with personal religiosity, both among men and women (OR=.88 ; OR=.89 ; p<.05, respectively). Among men, condom use at most recent sexual intercourse was related to parental education (OR=.38, p<.05), but its far stronger predictor, affecting women as well, was condom use at first sex (ORFEMALE=8.0 ; ORMALE=8.1 ; P<.01). Consistent condom use was also strongly associated with condom use at first intercourse (ORFEMALE=4.1 ; ORMALE=4.4 ; P<.01) and, to a lesser degree, with age (ORFEMALE=.74 ; ORMALE=.83 ; P<.01) and parental education (the later only among women ; OR=.15, p<.05). Discussion and conclusion. Religiosity seems to bear a marginal direct effect on sexual risk-taking among young Croatians. The absence of (strong) influences might be governed by two distinct phenomena. One has to do with a cultural role that the Catholic religion plays in Croatia, serving as a marker of ethno-national identity rather than a moral guidance. In addition, decline of traditional religiosity may be explained by increasingly permissive and highly sexualized popular culture.